Teaching of professionally oriented foreign language on the basis of a competency-based approach in technical universities - Kostyria, Iryna; Fandieieva, Alina (Національний технічний університет "Харківський політехнічний інститут", 2020)
The article reveals the implementation of a competency-based approach in the process of teaching of professionally oriented foreign language makes it possible to ensure the integrity of professional training of future professionals and the implementation of the Law of Ukraine “On Higher Education”. The main directions of implementation of a competency-based approach in the process of teaching of business foreign language to future specialists of technical universities have been determined: updating of a target-oriented component and improving the substantial component in a system of professionally oriented training of foreign language; reorientation of the educational process from knowledgeoriented one to practice-oriented one; determination of learning outcomes in the form of foreign language competencies formed in student; application of such educational technologies that would contribute to the creation of educational and professional situations, the main purpose of which is to ensure the formation of certain foreign language competencies in students during the educational process.

В статті з’ясовано, що реалізація компетентнісного підходу в процесі викладання професійно спрямованої іноземної мови дає можливість забезпечити цілісність професійної підготовки майбутнього фахівця та імплементацію Закону України “Про вищу освіту”. Визначено основні напрями реалізації компетентнісного підходу під час викладання ділової іноземної мови майбутнім фахівцям технічних університетів: оновлення цільового та удосконалення змістового компонентів системи іншомовної професійно спрямованої підготовки; переорієнтація освітнього процесу із знаннєво-орієнтованого на практико-орієнтований; визначення результатів навчання у вигляді сформованих у студента іншомовних компетенцій; використання у навчальному процесі таких освітніх технологій, які б сприяли створенню навчальних та професійних ситуацій, основною метою яких є забезпечення формування у студентів певних іншомовних компетентностей.
Викладання професійно спрямованої іноземної мови на засадах компетентнісного підходу у технічних університетах
Keywords: foreign language training; foreign language communicative competence; іншомовна комунікативна компетенція; іншомовна комунікативна компетентність